Iron-Sulfur Cluster Assembly in Trypanosoma brucei - Haindrich, Alexander Christoph (Jihočeská univerzita, 2013)
In this thesis we investigated genes of the Cytosolic Iron sulfur cluster assembly (CIA) pathway in T. brucei procyclic and blood-stream form for their possible functional redundancy. For this, RNAi double knockdown plasmids were generated containing knockdown partners which were selected based on the proposed model of the CIA pathway in S. cerevisiae. The generated plasmids were transfected into T. brucei cells, and growth effects on the transfectants upon tetracycline induced RNAi was measured.
Iron-Sulfur Cluster Assembly in Trypanosoma brucei
Keywords: Iron Sulfur Cluster; CIA; RNAi; Trypanosoma brucei; Iron Sulfur Cluster; CIA; RNAi; Trypanosoma brucei